A fungicide dresser against fungal phyto-pathogens of narrow-leaf lupin - L. I. Pimokhova; G. L. Yagovenko; Zh. V. Tsarapneva; N. V. Misnikova (Аграрная наука Евро-Северо-Востока)
The laboratory and field study of the dresser Delete Pro SC (suspension concentrate) effectiveness against anthracnose agent and other lupin diseases was carried out in Bryansk region in 2019-2021. Seeds, seedlings and sowings of the narrow-leaf lupin of Vityaz variety were the objects for the research. In the laboratory the effectiveness of Delete Pro (piraclostrobine 200 g/l) was tested in three doses of use (0.5; 1.0 and 1.5 l/t). Biological effectiveness was estimated by the number of infected seedlings grown in paper-and- polyethylene rolls compared to the control (without treatment). The dose 1.5 l/t had the high biological effectiveness against anthracnose (99.4 %). The total germination and the number of seeds with strong seedlings made 99.6 % and 90.4 %, respectively. The length of the roots and hypocotyl of the seedlings reliably increased by 9.4 and 10.6 mm, respectively. In the field test the seeds were treated with 1.5 l/t Delete Pro a month before sowing. The effectiveness of the fungicide was compared to the control variant without treatment. The average dresser biological effectiveness against anthracnose seed infection was 94.3 % during tests years. By the stage of brilliant pod the infected pods number decreased to 3.2 compared to 21.1 % in the control. Fusarium infection decreased from 20.1 % in the control to 13.7 % in the variant; risoctonia solari infection decreased from 9.4 % to 3.0 %. The development of Botrytis blight on the pods decreased 2.8 times. The significant true (LSD05 = 0.82) increasing of seed germination made 13.3 % and survival of productive plants by the harvest period increased by 32.4 %. Due to the application of the fungicide dresser Delete Pro SC (1.5 l/ha), the significant seed yield rise was 0.75 t/ha (LSD05 = 0.03); the cost recovery was 5.11 rubles.